Voluntary Exercise Prevents Lead-Induced Elevation of Oxidative Stress and Inflammation Markers in Male Rat Blood - Mustafa Mohammadi; Rana Ghaznavi; Rana Keyhanmanesh; Hamid Reza Sadeghipour; Roya Naderi; Hossein Mohammadi (The Scientific World Journal)
Regular mild exercise enhances antioxidant and anti-inflammatory systems of the body. The present study investigates voluntary exercise effects on lead toxicity as a known oxidative stressor. Male Sprague-Dawley rats were randomly divided into 2 groups. Sedentary control: the animals were housed 7 weeks in the regular cages. Exercise group: the animals were housed 7 weeks in the running wheel equipped cages, that is, the animal model of voluntary exercise. During the 7th week, all animals were administered lead acetate. Blood samples were collected at the end of the 6th week and 7th week (before and after lead administrations). Glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), and tumor necrosis factor (TNF-α) were measured in the samples. Our results showed that lead administration reduced blood SOD, GPx and CAT and increased TNF-α; in the controls, but in the exercise group, changes were not statistically significant. MDA in both groups increased after lead injections but it was significantly lower in exercise group compared to the sedentary animals. We concluded that voluntary exercise may be considered as a preventive tool against lead-induced oxidative stress and inflammation.